A CASE ON EMPLOYABILITY AND WORK LIFE BALANCE ISSUES OF WORKING WOMEN IN INDONESIA - PANKKHURRI SEMWAL (AIBPM Publisher, 2018)
Indonesia - a diverse nation of more than 300 ethnic groups. The largest economy in Southeast Asia. At present, Indonesia is the world’s fourth most populous nation, the world’s 10th largest economy in terms of purchasing power parity. Out of a total population of 252 million, more than 28 million people in Indonesia are still living below the poverty line. Approximately 40% of the total population of the country remains vulnerable of falling into poverty, as their income hover marginally above the national poverty line. Which can be largely be because of the slower pace of job creation as another challenge to efforts at reducing poverty, largely affecting the 1.7 million youth who enter the workforce each year. While there have been greater efforts at improving basic public services, the quality of health clinics and schools is uneven by middle income standards, contributing to alarming indicators, particularly in health.